경상북도 해외농업개발 추진방향 - 허장 (한국농촌경제연구원, 2009)
It has become widely understood that domestic agriculture needs to go abroad to explore international markets, and the Korean government has also started searching for resources in other countries for new growth driving force. The exploration should be pursued under the medium- or long-term perspectives as well as with proper strategies. Gyeongsangbuk-do Province has special concern for international agricultural development; it is in particular needed to secure raw materials of animal feeds considering the importance of livestock industry in the Province. To build bases in foreign countries on which farmers and agri-business persons from the Province start their businesses is also a critical task for growth of provincial economic activities. This study suggests, as long-term objectives of international agricultural development of the Gyeongsangbuk-do Province, (i) to enhance global competitiveness of regional economy, (ii) to create agricultural investment models which would be mutually beneficial to both parties, and (iii) to increase profitability of provincial agriculture and agriculture-related industries, such as the industries of livestock feeds, agricultural processing, and equipments and inputs. Two basic principles are also suggested to attain those objectives. First, key crops and countries should be identified for strategic investment. Crops will be selected based on how to market the products, while the places of investment are decided in consideration of the situation of production and marketing infrastructure as well as political conditions of the country. Step-by-step involvement is critical; investment in marketing facilities first, and the farm land second, or experimental farming first, and direct farming second, are the basic principle of the international agricultural development for the Province. Second, the public agencies support the private farmers and agri-business enterprises. During the period of decreased or stable crop price, the public sectors provide aids for building agricultural infrastructure and facilities like storage or dryer, implement surveys for agri-business environment, support for rural development, or sign MOU, which would form bases on which future private involvement can be made. When the international prices of agricultural products skyrockets, public agencies need to raise financial assistances so that private sectors are encouraged to go abroad. In-depth country analyses are provided for Mongolia, Cambodia, the Philippines, and Primorsky of Russia. Natural and therefore farming conditions in Mongolia are substantially strange to Korean farmers, meaning that the process of experimental farming is a first requirement. Production of high value-added products with high productivity under new techniques and intensive farming in small area will be a right decision in the first place. Small-scale simple storage facilities are needed in Mongolia because farming period is very short and farms are scattered here and there while physical infrastructure is not well developed. Gyeongsangbuk-do Province should aim to secure animal feed resources, for instance, corn, in Cambodia, but in the long-term, because of its low level of development of infrastructure and productivity as well as institutional backwardness of the country. To build dryer and storage facilities at key corn fields will be of great help for developing Cambodian corn industry. The second stage experimental farm may be built on a lease land of International Corn Foundation (ICF). After quarantine conditions are satisfied for import and enough quantity of corn is secured from farms, investment in collection, distribution, and export facilities in ports will be encouraged. For institutional support for international agricultural development, the following points are recommended. First, in Province office, a new organization called "International Agricultural Development Cooperation Task Force" to be formed under the leadership of Vice Governor. It will coodinate international agricultural development and cooperation projects in the Province. Collaborative relationships should be established between the public and private sectors including the organizations such as Provincial Rural Development Agency, Daegu-Gyeongsangbuk-do Provincial Research Institute, university institutes, and agri-business corporations. Financial and fiscal assistances for sound and promising enterprises need to be based not on the possibility of domestic imports of foreign products but on that of successful business. Technical consultation services, opening and expansion of educational courses for human capacity building as well as network formation for information sharing are not to be neglected. The Province should put many efforts to form comprehensive and collaborative relationships with the promising countries by, for instance, signing MOU with central or local governments.